Training Management Skills in The Field of Event Organizer at Sumber Bahagia Sentosa, Malang City - Salim, Agus; Hidayati, Nur; Asiyah, Siti (Journal of Educational Sciences, 2025)
Sentosa Happy Spring is one of the event organizers are developing in Malang City, but the problems that often arise met is management of one obstacle the main thing that often faced by the perpetrator event organizer. Activities This aiming For increase quality management in field event organizer Sumber Bahagia Sentosa so that it can reach target organization with method effective and efficient. The method used is descriptive with observation, mentoring and evaluation techniques. The results of the activities This show that mentoring and training in improving management quality has a significant positive impact on business actors. Through this assistance and training, it helps MSMEs overcome problems in business management, with an emphasis on the importance of customer service. MSMEs gain an understanding of how to improve management and communicate with customers. This training also improves the quality of human resources (HR) and MSMEs' confidence in interacting with customers, even though they still have limitations in human resource management capabilities.